The associations of early specialization, sports volume, and maturity status with musculoskeletal injury in elite youth football players - Li, Xiang; Feng, Runze; Luo, Shiyi; Li, Chunman; Gómez-Ruano, Miguel A. (Frontiers in Physiology, 2023)
Background: Youth football in schools has experienced rapid growth in China. Despite the increase of players engaging in more frequent, intensive, and organized sports training at their early ages, the controversy over early specialization (ES) still exists. This study aims to: a) investigate the training situation of players in the Chinese School Football Programme and b) examine the associations of early specialization, sports volume, and maturity status with musculoskeletal injury. Methods: A cross-sectional survey was used. Players who participated in the National School Football Winter Camp were invited to fill out a questionnaire that included the data of maturity, ES, sports volume, and injury history (n=88 boys and n=90 girls). Results: The results have shown that 80.3% of the athletes were classified as ES, while 19.7% of them were classified as non-ES. Almost all athletes (96%) participated in a sport for more than eight months in a year. Most athletes (75.8%) spent more than twice of the time on organized sports than leisure activities. 30.3% of the athletes trained on average more hours per week than the number of their ages. Binomial logistic regression models reflected the significant differences in the odds ratios (OR) of reporting a history of injury among athletes with different levels of specialization (p=0.024) and the OR of reporting a history of leg injury among players with different weekly sports volumes (p=0.038). Significant differences were also shown in the OR of players reporting foot injuries between players with different maturity state (p=0.046), and the Chi-squared test showed significant differences in the OR of reporting acute injuries between players with different levels of specialization (p=0.048) and weekly activity (p=0.022). No significant differences were found between the remaining variables. Conclusions: Most school football elite players follow the ES pathway despite the fact that ES increases the risk of injury, especially acute injury. Pre-pubertal and early pubertal players have a higher incidence of foot injuries. Players who train more hours per week than their ages have more leg injuries and acute injuries. Therefore, priority protection and intervention should be carried out for populations with a high risk of injury.